2018
DOI: 10.18203/2320-1770.ijrcog20181332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal and abnormal labour by using Modified WHO Partograph

Abstract: Background: Modified WHO partograph is graphical record of maternal and foetal data during progress of labour entered against time on single paper sheet. Entire labour can be interpreted in a glance on the photograph. It helps to detect abnormal progress of labour. It guides obstetrician to decide about the need for augmentation of labour or termination of pregnancy either by instrumental delivery or LSCS and avoids prolong labour before obstruction. The objectives were to study the course of normal and abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The second stage duration was 37.5% minutes and 26.3% minutes in primi and multigravidas respectively. The observation was very similar to a study conducted by Bhatt et al 10 In another study by Kunal Shinde et al, it was also found that multigravidae progressed faster than primigravidae. 11 In the present study, maximum number of cases before the alert line underwent normal vaginal delivery(84.2%) which is similar to a study by Javed et al, 8 but studies by Friedman E. and Shinde et al showed a higher incidence of 92.3% and 96.2% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The second stage duration was 37.5% minutes and 26.3% minutes in primi and multigravidas respectively. The observation was very similar to a study conducted by Bhatt et al 10 In another study by Kunal Shinde et al, it was also found that multigravidae progressed faster than primigravidae. 11 In the present study, maximum number of cases before the alert line underwent normal vaginal delivery(84.2%) which is similar to a study by Javed et al, 8 but studies by Friedman E. and Shinde et al showed a higher incidence of 92.3% and 96.2% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of fetal birth injuries was statistically lower among Group I than Group II (4%, 24%) p value= 0.009, as showen in Figure (2).…”
Section: Resultsmentioning
confidence: 79%